The Great Saphenous Vein—An Underrated Recipient Vein in Free Flap Plasty for Lower Extremity Reconstruction: A Retrospective Monocenter Study - Meiwandi, Abdulwares; Kamper, Lars; Küenzlen, Lara; Rieger, Ulrich M.; Bozkurt, Ahmet (Archives of Plastic Surgery, 2022)
Background Reconstruction of large soft tissue defects of the lower extremity often requires the use of free flaps. The main limiting factor and potential for complications lie in the selection of proper donor and recipient vessels for microvascular anastomosis. While the superficial veins of the lower leg are easier to dissect, they are thought to be more vulnerable to trauma and lead to a higher complication rate when using them instead of the deep accompanying veins as recipient vessels. No clear evidence exists that proves this concept.Methods We retrospectively studied the outcomes of 97 patients who underwent free flap plasty to reconstruct predominantly traumatic defects of the lower extremity at our institute. The most used flap was the gracilis muscle flap. We divided the population into three groups based on the recipient veins that were used for microvascular anastomosis and compared their outcomes. The primary outcome was the major complication rate.Results Overall flap survivability was 93.81%. The complication rates were not higher when using the great saphenous vein as a recipient vessel when comparing to utilizing the deep concomitant veins alone or the great saphenous vein in combination to the concomitant veins.Conclusions In free flap surgery of the lower extremity, the selection of the recipient veins should not be restricted to the deep accompanying veins of the main vessels. The superficial veins, especially the great saphenous vein, offer an underrated option when performing free flap reconstruction.
Keywords: microsurgery; free tissue flaps; reconstructive surgical procedures; lower extremity